Cross-correlation based high resolution electron backscatter diffraction and electron channelling contrast imaging for strain mapping and dislocation distributions in InAlN thin films. (15th February 2017) - Vilalta-Clemente, A.; Naresh-Kumar, G.; Nouf-Allehiani, M.; Gamarra, P.; di Forte-Poisson, M.A.; Trager-Cowan, C.; Wilkinson, A.J.
Abstract: We describe the development of cross-correlation based high resolution electron backscatter diffraction (HR-EBSD) and electron channelling contrast imaging (ECCI), in the scanning electron microscope (SEM), to quantitatively map the strain variation and lattice rotation and determine the density and identify dislocations in nitride semiconductor thin films. These techniques can provide quantitative, rapid, non-destructive analysis of the structural properties of materials with a spatial resolution of order of tens of nanometers. HR-EBSD has a sensitivity to changes of strain and rotation of the order of 10 −4 and 0.01° respectively, while ECCI can be used to image single dislocations up to a dislocation density of order 10 10  cm −2 . In the present work, we report the application of the cross-correlation based HR-EBSD approach to determine the tilt, twist, elastic strain and the distribution and type of threading dislocations in InAlN/AlN/GaN high electron mobility transistor (HEMT) structures grown on two different substrates, namely SiC and sapphire. We describe our procedure to estimate the distribution of geometrically necessary dislocations (GND) based on Nye-Kroner analysis and compare them with the direct imaging of threading dislocations (TDs) by ECCI. Combining data from HR-EBSD and ECCI observations allowed the densities of pure edge, mixed and pure screw threading dislocations to be fully separated. Graphical abstract: Image 1